Social capital and its influence on sustainable economic development and natural resource management among ethnic minorities in Phu Tho province, Vietnam - Van Khoat Vu; Kim Hanh Vu; Thi Thu Nga Vu (PLoS ONE, 2026)
This study investigates the role of social capital in promoting sustainable economic development and natural resource management among ethnic minority communities in Tan Son and Thanh Son districts, Phu Tho province, Vietnam. Located near Xuan Son National Park, these communities depend on natural resources and are increasingly involved in ecotourism. Using a mixed-methods approach, data were collected from 355 households through surveys, interviews, and focus groups. Results show high levels of mutual trust (80.6%) and close interpersonal relationships (71%), which facilitate collective action and information sharing. Participation in social organizations – particularly the Farmers’ and Women’s Unions – plays a crucial role in mobilizing community efforts and enhancing environmental awareness. However, information exchange remains mostly within family and ethnic lines, reflecting limited bridging capital. A linear regression model confirms that trust, social ties, and organizational involvement are significantly associated with household participation in forest management. While bonding capital is positively related to internal cohesion, weak external linkages may hinder broader collaboration and innovation. The study found that enhancing social capital, especially bridging and linking forms, is statistically linked to advancements in inclusive and sustainable development in buffer zones of protected areas.